UZALEŻNIENIE OD INTERNETU JAKO JEDNA Z PRZYCZYN ROZWODU - Kosek, Mirosław (Zeszyty Prawnicze, 2017)
Addiction to Internet as a Possible Reason of Divorce Summary The article deals with problem of the addiction to the Internet as one of possible reasons of divorce. In the first part – theoretical – the Author tries to describe the phenomenon of addiction, its phases and consequences. In the second part there have been presented a results of the researches of the influence of addictions to the Internet on the quality of the relationshipbetween spouses. The conclusion is that the Internet can be the cause of addiction. Its influence on relationship between the spouses can be destructive, it can lead to conflicts and finally to divorce. The Author postulates of all-Polish researches on the scale of this phenomenon and its negative social effects.